2013
DOI: 10.1186/2251-6581-12-60
|View full text |Cite
|
Sign up to set email alerts
|

Review of the mechanism of cell death resulting from streptozotocin challenge in experimental animals, its practical use and potential risk to humans

Abstract: Streptozotocin (STZ) (2-deoxy-2-({[methyl(nitroso)amino]carbonyl}amino)-β-D-glucopyranose) is a naturally occurring diabetogenic compound, produced by the soil bacterium streptomyces achromogenes, that exhibits broad spectrum of antibacterial properties. Streptozotocin functions as a DNA synthesis inhibitor in both bacterial and mammalian cells. In mammalian cells, the actual mechanism and metabolic targets of STZ toxicity that results in cell death is not known. This review identifies four key areas that expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
256
0
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(316 citation statements)
references
References 49 publications
(63 reference statements)
6
256
0
23
Order By: Relevance
“…Moreover, STZ is also known to be toxic to the liver as the liver expresses glucose 2 transporter (Eleazu et al, 2013b). Any one or a combination of these two factors could have accounted for the liver growth demonstrated by the diabetic control in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, STZ is also known to be toxic to the liver as the liver expresses glucose 2 transporter (Eleazu et al, 2013b). Any one or a combination of these two factors could have accounted for the liver growth demonstrated by the diabetic control in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, the blood glucose level in DM + HPE group was significantly lower (p<0.05) compared to DM group (Figure 2). STZ-induced diabetes is a well-established diabetic rat model, where the mechanism involves DNA fragmentation, nitric oxide (NO) and free radicals production which then lead to pancreatic β cells damage followed by reduction in insulin secretion (Eleazu et al, 2013). In diabetes, reduced body weight is due to loss of proteins and lipid as a result of proteolysis and lipolysis (Hebert & Nair, 2010).…”
Section: Effects Of Hpe On Body Weight and Blood Glucosementioning
confidence: 99%
“…The use of STZ in another study was followed by degenerative changes in proximal tubules that were partially consistent with our findings (36). It has been shown that STZ produces free radicals, which can cause damage to the kidney tissue along with diabetes (37). Also, the extract alone induced pathological changes in the kidney that was probably due to toxins as well as the excessive duration of the treatment period.…”
Section: Discussionmentioning
confidence: 99%